Managing cybersecurity in local governments: 2022 - Donald F. Norris PhD; Laura K. Mateczun JD (Journal of Cybersecurity Education, Research & Practice)
This paper, based on data from our second nationwide survey of cybersecurity among local or grassroots governments in the U.S., examines how these governments manage this important function. As we have shown elsewhere, cybersecurity among local governments is increasingly important because these governments are under constant or nearly constant cyberattack. Due to the frequency of cyberattacks, as well as the probability that at least some attacks will succeed and cause damage to local government information systems, these governments have great responsibility to protect their information assets. This, in turn, requires these governments to manage cybersecurity effectively, something our data show is largely absent at the American grassroots because, on average, local governments fail in to manage cybersecurity well. After discussing our findings, we conclude and make recommendations for ways to improve local government cybersecurity management.